2020
DOI: 10.1183/13993003.00441-2020
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of short- and long-term changes in lung function in cystic fibrosis using129Xe MRI

Abstract: Introduction129Xe ventilation MRI is sensitive to detect early CF lung disease and response to treatment. 129Xe-MRI could play a significant role in clinical trials and patient management. Here we present data on the repeatability of imaging measurements and their sensitivity to longitudinal change.Methods29 children and adults with CF and a range of disease severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 48 publications
0
43
0
Order By: Relevance
“…For most patients in the current study however (85%), the CPET caused a visible change in ventilation. Given the high intra-session repeatability of 129 Xe VDP (25), this suggests that the changes we observed in VDP and in the distribution of ventilation, relate to the underlying CF pathophysiology, and in part are likely a consequence of mucus movement in the airways. Change in VDP was greater than the intra-session repeatability of VDP, and therefore significant, for 45% of the patients assessed with 129 Xe.…”
Section: Discussionmentioning
confidence: 82%
“…For most patients in the current study however (85%), the CPET caused a visible change in ventilation. Given the high intra-session repeatability of 129 Xe VDP (25), this suggests that the changes we observed in VDP and in the distribution of ventilation, relate to the underlying CF pathophysiology, and in part are likely a consequence of mucus movement in the airways. Change in VDP was greater than the intra-session repeatability of VDP, and therefore significant, for 45% of the patients assessed with 129 Xe.…”
Section: Discussionmentioning
confidence: 82%
“…A contemporaneous CT could provide confirmation of disease phenotype and aid in the interpretation of 129 Xe findings, as illustrated by recent work by Myc et al 20 Third, the repeatability of 129 Xe MRI ventilation measurements in COPD has not been well characterized, limiting our ability to determine a clinically meaningful change in ventilation metrics. Previous studies have showed high repeatability for 129 Xe measurements of VDP in asthma 4 and cystic fibrosis, 42 and analogous studies are needed for COPD. Further, while the RBC to barrier ratio is known to be more robust to lung inflation than those measurements taken individually, 43 it is not possible to tell whether changes in this ratio are the result of changes in RBC, barrier, or both; thus we have elected here to report the two as separate measurements.…”
Section: Limitationsmentioning
confidence: 97%
“…129 Xe ventilation MRI response to therapy has been demonstrated in: patients with asthma after bronchodilator inhalation [163] and bronchial thermoplasty [312] , children with CF after pulmonary exacerbation and subsequent treatment with intravenous antibiotics [170] , patients with CF after acute maximal exercise [313] , patients with bronchial stenosis after airway stent placement [171] , and a patient with adenocarcinoma after radiotherapy [172] . In a study monitoring response to antibiotics in children with CF, 129 Xe VDP showed the largest relative improvement of all outcome measures [170] , and 129 Xe ventilation MRI has been shown to be a sensitive method to assess longitudinal lung disease in children and adults with CF [158] , [314] . Increased 129 Xe ventilation heterogeneity at low lung inflation levels, consistent with airway closure, has been noted in healthy elite divers who were able to exhale beyond the residual volume of the lungs [173] , and in healthy volunteers [174] , emphasising the need to control for lung inflation level to ensure reliable longitudinal ventilation imaging.…”
Section: Ventilation Imagingmentioning
confidence: 99%